When is ambiguity-attitude constant? - Eichberger, Jürgen; Grant, Simon; Kelsey, David (Journal of risk and uncertainty, 2012)
This paper studies how updating affects ambiguity attitude. In particular we focus on generalized Bayesian updating of the Jaffray-Philippe sub-class of Choquet Expected Utility preferences. We find conditions for ambiguity attitude to be the same before and after updating. A necessary and sufficient condition for ambiguity attitude to be unchanged when updated on an arbitrary event is for the capacity to be neo-additive. We find a condition for updating on a given partition to preserve ambiguity attitude. We relate this to necessary and sufficient conditions for dynamic consistency. Finally, we study whether ambiguity increases or decreases after updating.
Gesehen am 18.06.2019